If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 2) = 55 Reorder the terms: 5(2 + 3x) = 55 (2 * 5 + 3x * 5) = 55 (10 + 15x) = 55 Solving 10 + 15x = 55 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 15x = 55 + -10 Combine like terms: 10 + -10 = 0 0 + 15x = 55 + -10 15x = 55 + -10 Combine like terms: 55 + -10 = 45 15x = 45 Divide each side by '15'. x = 3 Simplifying x = 3
| 3y-4=5y+3 | | 3(x-4)(x+2)=2(x^2+2x+2)+x(x-3) | | -12+3=0 | | 81t^3-25t=0 | | x*2-x-49=6 | | (x-6)(2x+2)=(x+6)(x-2) | | 4(x+1)=4x+3 | | 2x^2+15x+18= | | 5x-8x-12-6=0 | | x*2-x-22=5 | | x*2-x-9=4 | | x*2-x-3=3 | | 2/3+15=17 | | x*2-x-0.5=2 | | z^2-36z=0 | | 2y+5=27 | | 1.5h(48)=634.40 | | 7(y+4)=2y-17 | | X-1+3x=15 | | 7x-2=4x+7 | | ln(5-6x)= | | 8h-2/9=6 | | 31x-16-19x=4(3x-5)+4 | | 15+3x=45 | | r^2-10r-750=0 | | 1x+1=-7x+9 | | 2(7-h)=-12 | | 1.5h+40(48)=634.40 | | 2(2y+1)+4y=3 | | 7(-3p+2)=35 | | 6+2x=22 | | 4lnx=12 |